PERTANGGUNGJAWABAN HUKUM TENAGA MEDIS DALAM KASUS MALAPRAKTIK: TINJAUAN PUSTAKA ATAS STANDAR PROFESI DAN ETIKA KEDOKTERAN - Benny Hartono; Yeti Indrawati (Jurnal Salome : Multidisipliner Keilmuan, 2025)
This study discusses the forms of legal liability of medical personnel in cases of malpractice based on a literature review of professional standards and medical ethics in Indonesia. Medical malpractice issues often lead to legal uncertainty, both for patients as victims and medical personnel as perpetrators, necessitating a thorough analysis of the applicable liability mechanisms. This study employs a normative legal method with an approach based on legislation and relevant literature. The results of the study indicate that the legal liability of medical personnel in cases of malpractice can take the form of criminal, civil, or administrative sanctions, with professional standards and medical ethics codes as the primary parameters for assessment. The role of professional organisations such as the Medical Ethics Honorary Council (MKEK) is crucial in the resolution of cases, both as an initial filter before formal legal proceedings and in professional ethics training. However, to date, there are no specific regulations that comprehensively govern the legal liability of medical personnel in cases of malpractice. Therefore, there is a need to strengthen regulations and coordination between institutions to ensure that legal protection for patients and medical personnel is balanced and fair.